Constituents of Ophthalmic Preparations - Lyle, W.M; Dean, T.W.; Doughty, M (Canadian Journal of Optometry, 2021)
Eyedrops are sterile aqueous liquids, usually solutions or suspensions of electrolytes and polymers with additional ingredients. The ophthalmic preparations discussed here are designed for instillation into the conjunctiva! cul-de-sac and must be initially sterile. Preparations used to clean or disinfect contact lenses are not intended for direct application to the eye. Ophthalmic preparations usually contain pharmaceutical adjuvants such as antioxidants, buffers, complexing agents, excipients, preservatives, stabilizing agents, suspending agents, tonicity agents and viscosity enhancers that are designed to assist in the formulation or stability of the product rather than for their therapeutic effect. The properties of some adjuvants enable them to perform several functions even though the specific substance is incorporated mainly for one of its roles.